Extraction of Keratin degrading enzyme from marine Actinobacteria of Nocardia sp and their antibacterial potential against oral pathogens - Haripriya Arun Subash; K. Santhosh; Kamala Kannan; Sivaperumal Pitchiah (Oral Oncology Reports)
Nocardia sp. thrives in challenging environmental conditions, particularly in salt-rich soils and marine ecosystems. This research aims to highlight its biological characteristics and recent applications in oral treatment. The organism is known to withstand extreme temperatures and pH levels, with some strains being associated with marine organisms, while others are implicated in human diseases. Additionally, it synthesizes enzymes of biotechnological importance. The bioactive compounds and enzymes derived from this marine actinobacterium not only demonstrate to its metabolic capabilities but also suggest its potential economic value. In this research, the keratin-degrading enzyme of Nocardia sp. showed the highest antimicrobial activity at a concentration level of 100 μg/ml against oral pathogens such as Streptococcus mutans, Salmonella typhi, and Klebsiella pneumoniae.